Voices from a Pandemic (Cell Rep Med, 2020)
Our many voices form the human chorus. Here, we present six diverse perspectives that share a common thread: how COVID-19 has changed our lives. We hear about the difficulties of providing palliative care on the front, the challenges patients seeking gender-affirming surgeries face, the loss of rituals built into healthcare visits, the pivots researchers take to study SARS-CoV-2, as well as the unique mental health impact of an ongoing trauma. These are but a few of the myriad voices that represent our COVID-19 collective. Yet they highlight a reality: a pandemic not only touches all people, but also elicits responses we never quite imagined.